Medieval Pilgrims and Modern Tourists: Walsingham (England) and Meryem Ana (Turkey). (7th April 2017) - Cusack, Carole
Abstract : This article examines the Marian shrines of Walsingham (England) and Meryem Ana (Turkey). Walsingham was a popular pilgrimage site until the Reformation, when Catholic sacred places were disestablished or destroyed by Protestants. Meryem Ana is linked to Walsingham, in that both shrines feature healing springs and devotion to the cult of the "Holy House" of the Virgin Mary. Walsingham is now home to multi-faith pilgrimages, New Age seekers and secular tourists. Meryem Ana is a rare Christian shrine in Islamic Turkey, where mass tourists rub shoulders with devout Christians supporting the small Greek Catholic community in residence. This article emerged from the experience of walking the Walsingham Way, a modern route based on the medieval pilgrimage in 2012, and visiting Meryem Ana in 2015 while making a different pilgrimage, that of an Australian attending the centenary of the Gallipoli landings. Both shrines are marketed through strategies of history and heritage, making visiting them more than simply tourism. Both sites offer a constructed experience that references the Middle Ages and Christianity, bringing modern tourism in an increasingly secular world into conversation with ancient and medieval pilgrimage and the religious past.